A Europa invade o sertão: o impacto da chegada de imigrantes italianos na cidade de Jaú (1853-1914) - Flávia Arlanch Martins De Oliveira (Caravelle)
We try to show what were the life conditions in the town of Jaú’s initial settlement, in the interior of São Paulo’s state. Afterwards, we deal with the elements which brought about developement in this region : the coffee expansion, the coming of railways and the installation of italian immigrates in the city. We put the accent on the part this immigrates played in Jaú’s modernisation and on the integration process between this newcomers and the caipira’s society which welcomed them.